2010
DOI: 10.1177/147323001003800331
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Actin-binding Proteins Indicates that Cofilin and Fascin are Related to Breast Tumour Size

Abstract: This study was designed to investigate the expression of four actin-binding proteins, a-actinin-4, cofilin 1, fascin and elongation factor 1-a 2 (eEF1A2), in samples of breast cancer from 112 patients with different stages of breast cancer (stages T0 -T1, T2 and T3) compared with normal control tissues (n = 33). Levels of eEF1A2 and aactinin-4 mRNA appeared to be unrelated to tumour size, except for a significant down-regulation of a-actinin-4 mRNA in T3 cases. Significant up-regulation of cofilin 1 mRNA was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Specifically, we observed the down-regulation of the ACTN4 gene, which was also confirmed by the proteomic analysis. Even though the roles of ACTN4 in tumors reported in the literature are contradictory [29], [30] our data are in agreement with those of authors who demonstrated the role of ACTN4 gene in suppressing tumorigenicity in different tumor types [31][33]. Additionally, our data, showing the increase of some members of the 14-3-3 protein family, are in agreement with those of other authors, who demonstrated a positive role of such proteins in the induction of oncogenic transformation and in promoting cancer cell survival [34], [35].…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, we observed the down-regulation of the ACTN4 gene, which was also confirmed by the proteomic analysis. Even though the roles of ACTN4 in tumors reported in the literature are contradictory [29], [30] our data are in agreement with those of authors who demonstrated the role of ACTN4 gene in suppressing tumorigenicity in different tumor types [31][33]. Additionally, our data, showing the increase of some members of the 14-3-3 protein family, are in agreement with those of other authors, who demonstrated a positive role of such proteins in the induction of oncogenic transformation and in promoting cancer cell survival [34], [35].…”
Section: Discussionsupporting
confidence: 91%
“…We believe that these candidates are enriched in true positive results with a higher chance of experimental validation, but would have been overlooked if we had only considered individual gene associations, given their modest associations with breast cancer. This list supports previously well-studied breast cancer genes, such as the BRCA1 (breast cancer breast cancer 1, early onset) associated RING (really interesting new gene) domain 1 gene ( BARD1 ) [60,61], the mucin 1 ( MUC1 ) [62,63] or cofilin-1 genes ( CFL1 ) [64,65], but also suggest novel candidates that warrant further investigation in breast cancer. Some of these novel genes, such as CSNK2A1 , ARHGAP21 and PRKACA have already been somehow implicated (genetic association, differential expression and mutation studies) in others types of cancers, namely neck squamous carcinoma [48], colorectal cancer risk [50], lung squamous cell carcinoma [51] and pituitary tumors [49]; while others, such as PPP2R5A , have not been studied in cancer, but may represent good biological candidates, given the involvement of other members of the known tumor suppressor phosphatase 2A family in ovarian, uterine and breast cancer risk [66,67].…”
Section: Discussionsupporting
confidence: 81%
“…There was also no correlation observed between cofilin expression and tumor size. In contrast, another study demonstrated a positive association between cofilin expression and tumor stages T0, T1, and T2 (but not T3) in breast cancer (39). Resolution of this discrepancy requires additional study.…”
Section: Discussionmentioning
confidence: 87%